Rancang Bangun Sistem Penyusunan Portofolio dan CV Berbasis Visual Builder - Widyastutik, Luky; Airlangga, Primaadi (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
The problem of students who will and have graduated from college is in terms of job search, among others, their lack of understanding in making a CV with a good format so as to make opportunities accepted in a job a little. Design this system based on visual builder that is able to process data and facilitate storage automatically. This sample is obtained from observation data with the target of Unwaha students, this method is used because it has ease in finding an existing fact. The analytical technique used in this research is qualitative descriptive which is done by analyzing or describing the process and the results of the design of the developed system. Design this system based on visual builder that is able to process data and facilitate storage automatically. For that, there is a system that can facilitate the creation of a CV and Portfolio so that students no longer need to be dizzy in loading and publishing their CV.